Resolution all-Russian scientific-practical conference with international participation «Topical issues of prevention of communicable and non-communicable diseases: epidemiological, organizational epidemiological, organizational and hygienic aspects» - article Editorial (Эпидемиология и вакцинопрофилактика, 2023)
.